2006
DOI: 10.1063/1.2227625
|View full text |Cite
|
Sign up to set email alerts
|

Interface magnetism and magnetic structure of GdN∕Fe multilayers studied by x-ray magnetic circular dichroism

Abstract: Articles you may be interested inElectronic structure of Fe/MgO/Fe multilayer stack by X-ray magnetic circular dichroism Enhanced ferromagnetic moment in Co-doped BiFeO3 thin films studied by soft x-ray circular dichroism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…As a final note, although tangential to GdN, Leuenberger and co-workers [127] also found that Fe layers induce long-range magnetic order in GdN layer at temperatures above the T c of GdN in GdN/Fe multilayers.…”
Section: Experimental Studiesmentioning
confidence: 87%
“…As a final note, although tangential to GdN, Leuenberger and co-workers [127] also found that Fe layers induce long-range magnetic order in GdN layer at temperatures above the T c of GdN in GdN/Fe multilayers.…”
Section: Experimental Studiesmentioning
confidence: 87%
“…As a fi nal note, although tangential to GdN, Leuenberger and co-workers [127] also found that Fe layers induce long-range magnetic order in GdN layer at temperatures above the T c of GdN in GdN/Fe multilayers.…”
Section: Experimental Studiesmentioning
confidence: 87%
“…Examples can be found in [173], which reported that by adding a few per cent of magnetic ions such as Mn, the T c of GaN or ZnO well exceeds room temperature. Again mentioning the experiments on GdN/Fe multilayers [127] in this context, it is worth noting that the Fe layers are found to be responsible for the long-range magnetic order in the GdN layer at temperatures largely above T c .…”
Section: Enhancement Of the Transition Temperatures And Potential Devmentioning
confidence: 99%